2023
DOI: 10.1186/s12909-023-04166-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of student-centered flipped classroom in physiology education

Abstract: Background The flipped classroom approach has gained increasing popularity in medical education. Physiology is a basic medical course that studies the phenomena and laws of human life activities, and is a crucial link course connecting preclinical courses and clinical courses. However, there is a paucity of data showing the effectiveness of the flipped classroom model for the entirety of physiology course in medical undergraduate students. Method 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Проте дані щодо ефективності впливу цього методу на знання та навички дещо суперечливі -від негативних до позитивних, хоча сприйняття його студентами було переважно позитивним [41; 42]. У дослiдженнi Харбінського медичного університету студенти, що працювали за методом FC, отримуючи доступ до навчального матеріалу (відео, текст або презентація Power Point) до проведення аудиторного заняття, продемонстрували вищу успішність та кращу кореляцію поточних результатів з іспитовими оцінками, ніж студенти, які слухали звичайні лекції з фізіології, а потім отримували домашнє завдання, і вже не взаємодіяли з викладачем чи колегами [43]. Аналогічні результати були отримані під час порівняння успішності при вивченні різних тем або традиційним дидактичним, або перевернутим методом [44], так само як під час повного викладання курсу [45].…”
Section: Tetiana Zaporozhets Lidiia Korovina Tetiana Sukhomlyn Analys...unclassified
“…Проте дані щодо ефективності впливу цього методу на знання та навички дещо суперечливі -від негативних до позитивних, хоча сприйняття його студентами було переважно позитивним [41; 42]. У дослiдженнi Харбінського медичного університету студенти, що працювали за методом FC, отримуючи доступ до навчального матеріалу (відео, текст або презентація Power Point) до проведення аудиторного заняття, продемонстрували вищу успішність та кращу кореляцію поточних результатів з іспитовими оцінками, ніж студенти, які слухали звичайні лекції з фізіології, а потім отримували домашнє завдання, і вже не взаємодіяли з викладачем чи колегами [43]. Аналогічні результати були отримані під час порівняння успішності при вивченні різних тем або традиційним дидактичним, або перевернутим методом [44], так само як під час повного викладання курсу [45].…”
Section: Tetiana Zaporozhets Lidiia Korovina Tetiana Sukhomlyn Analys...unclassified
“…Teacher-student interaction and questionnaires were used to assess the students, and it found that the FC model improved student performance. Six studies [ 7 , 8 , 13 , 15 , 19 , 21 ] assessed students based on final exam scores. In each study, students were divided into two groups: one group was subjected to traditional teaching, while for the other group, various methods were used including videos and resource materials [ 7 , 8 , 19 , 21 ], self-study [ 13 ], and PowerPoint [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Six studies [ 7 , 8 , 13 , 15 , 19 , 21 ] assessed students based on final exam scores. In each study, students were divided into two groups: one group was subjected to traditional teaching, while for the other group, various methods were used including videos and resource materials [ 7 , 8 , 19 , 21 ], self-study [ 13 ], and PowerPoint [ 15 ]. Five studies [ 7 , 8 , 13 , 19 , 21 ] observed that FC is an effective tool for improving students' performance, while one study [ 15 ] did not observe any change in the students' performance.…”
Section: Reviewmentioning
confidence: 99%
“…A randomized controlled trial conducted by American scholars (Paul et al, 2023) showed that the flipped classroom significantly improves the clinical skills of medical students compared to online-only learning. A study from China (Lu et al, 2023) suggests that flipped classrooms improve students' course learning and promote higher-order ability-set acquisition; the researchers concluded that flipped classrooms allow a rationalized formative evaluation system. Wang (2017) summarized several lessons to promote flipped classrooms, including enhancing teachers' understanding of the merits of flipped classroom approach, establishing peer mentoring mechanisms, and effective teacher capacity building.…”
Section: Introductionmentioning
confidence: 99%